2020
DOI: 10.30684/etj.v38i11a.1714
|View full text |Cite
|
Sign up to set email alerts
|

Visual Depression Diagnosis From Face Based on Various Classification Algorithms

Abstract: Most psychologists believe that facial behavior through depression differs from facial behavior in the absence of depression, so facial behavior can be utilized as a dependable indicator for spotting depression. Visual depression diagnosis system (VDD) establishes dependents on expressions of the face that are expense-effective and movable. At this work, the VDD system is designed according to the Facial Action Coding System (FACS) to extract features of the face. The key concept of the Facial Action Coding Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Table 4 presents a comparative analysis of various studies proposed for depression detection through different methodologies. Nasser et al [39] developed a model for diagnosing depression from facial expressions, employing various learning algorithms and achieving an accuracy of 85% with the K-Nearest Neighbors (KNN) method. In a study, Katrakazas et al [40] explored depression detection using time-series classification, where they reported a high accuracy rate of 93.6% for their proposed method.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 presents a comparative analysis of various studies proposed for depression detection through different methodologies. Nasser et al [39] developed a model for diagnosing depression from facial expressions, employing various learning algorithms and achieving an accuracy of 85% with the K-Nearest Neighbors (KNN) method. In a study, Katrakazas et al [40] explored depression detection using time-series classification, where they reported a high accuracy rate of 93.6% for their proposed method.…”
Section: Discussionmentioning
confidence: 99%
“…The algorithms of NN are typically much faster than those of conventional iterative CF techniques. Additionally, the solution does not require an initial guess, and there is an ability to implement the designed network model with special-purpose hardware and, in this way, take advantage of the full ability of NN, including high processing speed [17][18][19][20].…”
Section: Fast Curve Fitting Using Neural Networkmentioning
confidence: 99%
“…This suggested approach is implemented using the principle of fast processing Curve Fitting (CF) executed by Neural Networks (NNs). NNs have been employed in various fields due to, in part, a new powerful algorithm development that affects their ability to process information rapidly and leads to faster response [17][18][19][20]. NNs provide a perfect tool with high accuracy and fast response solution for nonlinear CF problems [15].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the training phase of KNN saves the training set feature vectors with their related class labels. In the testing phase, the algorithm determines the K value, which can be estimated by trial and error and find out the optimal K value like 2,3 or 5, or it can be identified based on the dataset by using the following equation [14,15,16]:…”
Section: K-nearest Neighbor (Knn) Classifiermentioning
confidence: 99%
“…The algorithm determines the tested feature vector predicted class using the majority vote of the nearest neighbor's class, i.e., get the most frequent class from the nearest neighbors. The most repeated classes will be assigned to the testing feature vector record [14,15,17].…”
Section: K-nearest Neighbor (Knn) Classifiermentioning
confidence: 99%